Mapping the Digital Literacy of Pre-Service Biology Teachers as a Needs Analysis in Developing of STEM-Based Liveworksheets - Ika Rifqiawati; Desi Eka Nur Fitriana; Indah Juwita Sari; Yarfa Fadilah; Chanat Intakanok (JIPI (Jurnal IPA & Pembelajaran IPA), 2025)
Digital literacy is an essential competency for pre-service teachers in addressing the challenges of 21st-century learning, particularly in integrating technology with the science, technology, engineering, and mathematics (STEM) combined with problem based learning (STEM-PBL) approach. This study aims to map the digital literacy skills of pre-service biology teachers as a foundation for designing interactive learning media in the form of STEM-PBL-based liveworksheets. The research employed a descriptive quantitative approach involving students from a biology education program at an Indonesian university. The instrument used was a digital literacy questionnaire consisting of four main indicators: internet searching, hypertextual navigation, content evaluation, and knowledge assembly. The findings indicate that the participants’ digital literacy skills fall within the moderate to high categories, with varying results across indicators. The highest score was obtained in internet searching at 77% (high), followed by content evaluation at 71% (high). Meanwhile, hypertextual navigation reached only 56% (moderate), and knowledge assembly recorded the lowest score at 51% (moderate). These results suggest that while students are relatively proficient in accessing digital information, they still face challenges in navigating hypertext links and synthesizing diverse sources into new knowledge products. This mapping provides an empirical foundation for designing STEM-PBL-integrated liveworksheets that are adaptive to students’ needs. The implications highlight the necessity of strengthening hypertext navigation and knowledge assembly skills to enable pre-service biology teachers to fully leverage digital technologies in science education